2022
DOI: 10.3390/medicina58040546
|View full text |Cite
|
Sign up to set email alerts
|

A New Comorbidity in Periodontitis: Fusobacterium nucleatum and Colorectal Cancer

Abstract: There is very recent and strong evidence relating Fusobacterium nucleatum to colorectal cancer. In this narrative review, we update the knowledge about gingival dysbiosis and the characteristics of Fusobacterium nucleatum as one of the main bacteria related to periodontitis. We provide data on microbiome, epidemiology, risk factors, prognosis, and treatment of colorectal cancer, one of the most frequent tumours diagnosed and whose incidence increases every year. We describe, from its recent origin, the relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…This, together with the fact that oral bacteria were found as transcriptionally active in adenocarcinoma could explain why different subgingival pathogens (such as Parvimonas, Fusobacterium, Actinomyces, Campylobacter or Dialister among others) were detected in adenoma and adenocarcinoma samples through 16S rRNA metabarcoding bioanalysis. It has to be borne in mind that these oral microbes could promote a gut in ammatory effect, individually, as reported previously for P. micra [110] and for other bacteria [5,9,95,111,112] or synergistically when living in communities or aggregates [107].…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…This, together with the fact that oral bacteria were found as transcriptionally active in adenocarcinoma could explain why different subgingival pathogens (such as Parvimonas, Fusobacterium, Actinomyces, Campylobacter or Dialister among others) were detected in adenoma and adenocarcinoma samples through 16S rRNA metabarcoding bioanalysis. It has to be borne in mind that these oral microbes could promote a gut in ammatory effect, individually, as reported previously for P. micra [110] and for other bacteria [5,9,95,111,112] or synergistically when living in communities or aggregates [107].…”
Section: Discussionmentioning
confidence: 88%
“…When fastidious anaerobic bacteria, such as Parvimonas or other periodontal pathogens, arrive to the gut, they can settle at the base of villi or in intestinal crypts of Lieberkühn as well as in dysplastic structures of adenomas or adenocarcinomas where the oxygen pressure is low [95]. Consequently, the original oral P. micra could undergo different genomic rearrangements, accumulate mutations and promote changes in gene expression to adapt to its new niche such as the ones observed after the adenocarcinoma genome analysis performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fusobacterium nucleatum is an oral bacterium rarely found in healthy gut and colorectal cancer is a precondition for its colonization [ 8 ]. Several bacterial species have previously been linked to colorectal carcinogenesis [ 9 ] and recent studies even suggested a causal role for Fusobacterium nucleatum [ 4 , 10 , 11 ]. Although we were not able to verify the presence of Fusobacterium nucleatum in cancer tissue from our patient, we did not find an oral–gingival or other port of entry.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkable progress has been achieved in studies relating to gut microbiota and CRC, highlighting the distinguished value of diagnosis and therapeutic prediction of the gut microbiome (6,7). Bacterial strains such as Fusobacterium nucleatum, Escherichia coli, and Bacteroides fragilis are known for their tumor activities (8)(9)(10). However, there are many uncertainties concerning the association between gut microbiome and CRC, such as the huge number of bacteria (approximately 100 million) and distinct microbiota signatures, bacterial interactions, as well as geographical and race differences (11).…”
Section: Introductionmentioning
confidence: 99%